HOW PRIMARY SCHOOL TEACHERS DEVELOP THEIR PUPILS' MATHEMATICAL WORD PROBLEM SOLVING SKILLS - IULIANA MARCHIŞ (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. Problem solving is an important skill that all persons should possess. Mathematical word problems contribute for the development of the problem solving skill. These problems occupy an important space in primary school mathematical curriculum. Primary school teachers have to develop their pupils' mathematical word problem solving skills. The aim of this research is to study how primary school teachers solve mathematical word problems with their pupils. Three quarters of the teachers guide pupils in order to understand the problem and encourage them for self-control during problem solving. Only one third of the respondents encourage their students to solve the problems with more methods. Only half of the teachers ask their pupils to present the solution. Three quarters of the respondents have a positive attitude and guidance in case their pupils can't solve a problem. Almost three quarters of the primary school teachers give interesting, real life close problems in class. Teachers expect more from their pupils as regarding problem solving behaviour than they do.